2017
DOI: 10.1002/pd.5052
|View full text |Cite
|
Sign up to set email alerts
|

Nuchal translucency measurement, freeβ-hCG and PAPP-A concentrations in IVF/ICSI pregnancies: systematic review and meta-analysis

Abstract: So far, data on the effect of assisted reproductive technologies (ART) on the components of first trimester combined screening for Down syndrome are still controversial. A systematic search of the literature was performed in order to identify the effect of ART, particularly in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) with fresh embryo transfer, on the nuchal translucency, free beta-human chorionic gonadotrophin and pregnancy-associated plasma protein-A measurements. Moreover, a met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 53 publications
3
17
0
Order By: Relevance
“…As suggested by Fantasia et al [23], normality of placental perfusion and only abnormally low pregnancy-associated plasma protein-A and placental growth factor in the first trimester of CHDs suggests mild and subclinical placental dysfunction. This result is coherent with the recent finding of increased risk of CHD in pregnancy after assisted reproductive technologies, which presents also lower placental hormones in the first trimester [24,25]. This may be associated with other contributors explaining altered development in all CHD fetal systems, including the heart, brain, and placenta [23,26,27].…”
Section: Discussionsupporting
confidence: 89%
“…As suggested by Fantasia et al [23], normality of placental perfusion and only abnormally low pregnancy-associated plasma protein-A and placental growth factor in the first trimester of CHDs suggests mild and subclinical placental dysfunction. This result is coherent with the recent finding of increased risk of CHD in pregnancy after assisted reproductive technologies, which presents also lower placental hormones in the first trimester [24,25]. This may be associated with other contributors explaining altered development in all CHD fetal systems, including the heart, brain, and placenta [23,26,27].…”
Section: Discussionsupporting
confidence: 89%
“…A recent meta-analysis from our group showed that IVF/ICSI pregnancies present placental dysfunction with lower pregnancy-associated plasma protein A (PAPP-A) and higher free β-human chorionic gonadotropin concentrations in the first trimester 72 . Recent data also show that, in pregnancies with isolated major CHD, there is significantly lower PAPP-A and placental growth factor in the absence of impaired placental perfusion and increased risk of pre-eclampsia 73,74 .…”
Section: Discussionmentioning
confidence: 99%
“…First‐trimester combined screening in IVF/ICSI pregnancies obtained after fresh embryo transfer shows increased concentrations of free β‐human chorionic gonadotropin and a reduction in pregnancy‐associated plasma protein‐A. These biomarkers indicate abnormal placentation and may be the biochemical precursors of anomalous outcomes described in IVF/ICSI pregnancies.…”
Section: Discussionmentioning
confidence: 99%